A Multi-Agent Based Approach to Support Adaptability in Home Care Applications. Issue 10 (2015) - Armentia, A.; Gangoiti, U.; Priego, R.; Estévez, E.; Marcos, M.
Abstract: Health systems are evolving to cope with the increasing costs of providing high-level medical care to elderly people maintaining their quality of life. Smart homes, where ambient and biomedical sensors can coexist, have become a suitable approach to address the main goals of home care scenarios: preventive care, recognizing deteriorating health and allowing a personalized care. To achieve these goals, applications have to exhibit adaptability and availability among other characteristics. Adaptability allows tracking the patient's state as well as reacting to abnormal situations. Availability ensures the execution of the application under failure of processing devices. In order to meet these requirements, this paper proposes a general-purpose middleware architecture based on multi-agent technology that provides mechanisms to: develop customizable applications based on the separation of concerns principle; manage the execution of applications; support adaptability by means of event-based relationships among applications; ensure availability through the use of replicated agents. The performance of the proposed middleware is assessed in terms of reaction time to adapt to irregular situations for different availability levels (number of replicated agents) and number of application services.